Ginsenoside Rg1 Ameliorates Pulmonary Hypertension by Inhibiting cGAS/STING Mediated Cell Senescence - Ding R; Xie H; Zhang Y; Qin L; Peng G; Yi J; Tan J; Cao X; Zheng R; Dai A (Drug Design, Development and Therapy)
Rongzhen Ding,1– 3 Haiping Xie,4 Yu Zhang,2,3 Li Qin,3,5 Guoran Peng,2,3 Jian Yi,2,3 Junlan Tan,6 Xianya Cao,2,3 Runxiu Zheng,2,3 Aiguo Dai2 1Department of Health Management, The First Hospital of Hunan University of Chinese Medicine, Changsha, Hunan, 410021, People’s Republic of China; 2Department of Respiratory Diseases, Medical School, Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People’s Republic of China; 3Hunan Provincial Key Laboratory of Vascular Biology and Translational Medicine, Changsha, Hunan, 410208, People’s Republic of China; 4Department of Urology, The First Hospital of Hunan University of Chinese Medicine, Changsha, Hunan, 410021, People’s Republic of China; 5Laboratory of Stem Cell Regulation with Chinese Medicine and Its Application, School of Pharmacy, Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People’s Republic of China; 6Department of Gerontology, The First Hospital of Hunan University of Chinese Medicine, Changsha, Hunan, 410021, People’s Republic of ChinaCorrespondence: Aiguo Dai, Department of Respiratory Diseases, Medical School, Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People’s Republic of China, Tel +86 0731-88459072, Email daiaiguo@hnucm.edu.cnBackground: Pulmonary hypertension (PH) is a fatal pulmonary vascular disease that currently lacks effective treatment methods. Ginsenoside Rg1 has positive effects on improving PH, but its specific mechanism remains unclear.Purpose: This study was designed to investigate the molecular mechanisms of ginsenoside Rg1 in improving PH.Methods: The therapeutic efficacy of ginsenoside Rg1 in PH rat model was assessed using cardiopulmonary hemodynamic measurements and histopathological staining. Network pharmacology analysis was used to predict potential targets, and the expression of cyclic GMP–AMP synthase (cGAS)/stimulator of interferon genes (STING) pathway proteins was evaluated by immunofluorescence staining. Senescence marker gene transcription and protein levels were assessed by RT-PCR and immunohistochemistry, respectively. Finally, ELISA was employed to quantify senescence-associated secreted proteins (SASP).Results: Our results demonstrate that ginsenoside Rg1 significantly reduces right ventricular systolic pressure (RVSP). Ultrasound findings indicate that ginsenoside Rg1 increases the pulmonary artery acceleration time to pulmonary ejection time ratio (PAT/PET) and tricuspid annular plane systolic excursion (TAPSE), while reducing the right ventricular anterior wall thickness (RVAWT). Histological examination (HE) suggests that ginsenoside Rg1 significantly diminishes pulmonary vascular remodeling. Furthermore, ginsenoside Rg1 markedly decreases the mRNA and protein expression of the aging markers p21 and p16, as well as significantly reduces the NF-kB, IL-6, and IL-8.Conclusion: This study presents compelling evidence that ginsenoside Rg1 may enhance pulmonary vascular remodeling in PH by inhibiting cell senescence via the cGAS/STING signaling pathway.Keywords: ginsenoside Rg1, pulmonary hypertension, cGAS/STING signaling pathway, cell senescence, pulmonary vascular remodeling